2008
DOI: 10.1089/end.2008.0058
|View full text |Cite
|
Sign up to set email alerts
|

Construct Validity of the Pig Intestine Model in the Simulation of Laparoscopic Urethrovesical Anastomosis: Tools for Objective Evaluation

Abstract: Tests of performance time and postoperative leakage accurately reflected the subjects' degree of experience, indicating that this model for L-UVA provides an experience closely resembling the person's past experience and that the porcine intestine provides a valid model for simulating the procedure. Measuring volume of leakage from the anastomosis provides an objective measure of the quality of the anastomosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…Another model used for laparoscopic UVA is the porcine intestine model, which was also shown to have construct validity in the study carried out by Boon et al. . Jiang et al.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another model used for laparoscopic UVA is the porcine intestine model, which was also shown to have construct validity in the study carried out by Boon et al. . Jiang et al.…”
Section: Resultsmentioning
confidence: 99%
“…Another model used for laparoscopic UVA is the porcine intestine model, which was also shown to have construct validity in the study carried out by Boon et al [49]. Jiang et al [50] proposed the porcine model as a more effective, realistic and cheaper alternative to the chicken skin model for laparoscopic training.…”
Section: Animal Modelsmentioning
confidence: 99%
“…11 Standard box trainers consist of laparoscopic instruments, digital camera, monitor, light source and tissue-like materials. 17,18 There are also cheaper, more expensive and home-made options for training boxes. The principle of box trainers, however, has not changed.…”
Section: Discussionmentioning
confidence: 99%
“…This model was also previously described by Boon et al and it avoids the drawbacks of the previous model as it imitates the human tissue and it gives the impression of a real-life laparoscopic urethrovesical anastomosis. 21 In this task, we evaluated the trainees by the time needed to complete the anastomosis and by the amount of leakage after its completion. However, the analysis of the learning curve of the trainee showed that the improvement in the quality of the anastomosis was achieved before the improvement in the time needed to complete it.…”
Section: Discussionmentioning
confidence: 99%